Cooperation under the threat of expulsion in a public goods experiment - Matthias Cinyabuguma; Talbot Page; Louis Putterman (Brown University, Department of Economics, 2004)
In a public goods experiment with the opportunity to vote to expel members of a group, we found that contributions rose to nearly 100% of endowments with significantly higher efficiency compared with a noexpulsion baseline. Expulsions were strictly of the lowest contributors, and there was an exceptionally strong fall-off in contributions in the last period, when the expulsion threat was unavailable. Our findings support the intuition that the threat of expulsion or ostracism is one device that helps groups to provide public goods.
Keywords: C91; H41; D23; 330; Public goods; collective action; punishment; Öffentliches Gut; Test; Theorie